Correlation of Body Mass Index (BMI) with Forced Vital Capacity (FVC) and Forced Expiratory Volume 1 Second (FEV1s) in Adolescents - Polii, Hedison; Engka, Joice. N.A; Assa, Youla A. (JURNAL BIOS LOGOS, 2025)
The Respiratory System plays an important role for humans. The main function of the respiratory system is to obtain oxygen (O2) required by the body’s cells and to expel carbon dioxide produced by the cells. Body Mass Index (BMI) influences lung volume. Forced Expiratory Volume in 1 second (FEV1) is the lung capacity that includes the volume of air that can be forcefully exhaled in one second during a pulmonary function test. FEV1 is often used as an important parameter in evaluating lung function. This study aims to investigated the relationship between Body Mass Index (BMI) and Forced Vital Capacity (FVC), as well as Forced Expiratory Volume in 1 Second (FEV1), in adolescents. This research is an analytical observational study using a cross-sectional research design. Sampling was performed using purposive sampling techniques. Data collection involved measuring body weight and height to calculate BMI and measuring Forced Vital Capacity (FVC) using a spirometer. Data analysis was conducted using normality tests and Spearman’s correlation test. The study results revealed correlation between Forced Vital Capacity (FVC) and Body Mass Index in adolescents. Other results showed that there was no statistically significant relationship between Body Mass Index and FEV1s in adolescents.